Unveiling driving disparities between satisfaction and equity of ecosystem services in urbanized areas - Zhou Fang; Shi Xue; Qin Zhou; Changgao Cheng; Yang Bai; Zhongde Huang; Jie Wang; Ruibo Wang; Yixin Wang; Rong Wu; Jing Rong; Jun Hong; et al. (Resources, Environment and Sustainability)
Rapid urbanization intensifies the challenges of achieving satisfaction and equity in ecosystem services (ESs). Beginning with a theoretical overview, we identify five pivotal challenges in managing urban ESs, forming the basis for our integrative analysis. Employing a multi-level analytical perspective, our research quantifies ESs satisfaction through supply–demand ratios and evaluates ESs equity via supply–demand Gini coefficient. Simultaneously explored the driving force relationship between these two dimensions. This study uses Guangdong Province, a typical urbanized area in China, as a case study to assess the supply and demand relationships of four regulating ESs: water retention, soil retention, carbon storage, and water purification. Our results highlight the disparity in ESs management effectiveness across different scales while the overall assessments might suggest adequate or equitable ESs, localized assessments within cities and regions often uncover specific ESs issues. A pivotal aspect is that single-factor critical to ESs satisfaction or equity dimension may have limited or opposing importance in another, but interactive effects of multiple factors can effectively mitigate these divergent impacts through non-linear synergies. These insights not only reveal the multiplex impacts of natural–social–economic drivers on urban expansion but also guide the targeted development in different management scale, multi-dimensional management strategies to address these disparities. This approach enriches the discourse on sustainable urban development and provides a robust framework for addressing the nuanced challenges of urban ESs management.